Economic and non-economic returns to communist party membership in Vietnam. (October 2019) - Markussen, Thomas; Ngo, Quang-Thanh
Highlights: The paper investigates the determinants and effects of Communist Party membership in rural Vietnam. The analysis is based on household- and individual level panel data. Results show that Communist Party membership leads to higher income and easier access to credit. Communist Party members have much higher subjective wellbeing than others do. The positive effects of party membership are much stronger for men than for women. Abstract: Single-party political systems exist in a number of countries, such as China and Vietnam. In these countries, party membership is potentially an important source of economic and social status. This paper investigates these effects and the mechanisms behind them. In particular, we use household- and individual level panel data to analyze the causes and consequences of Communist Party membership in rural areas of Vietnam. Fixed effects models are employed to control for unobserved differences between party members and others. Results suggest that party membership has a moderate, positive effect on income, on the order of 7 percent, and a large, positive effect on subjective well-being, even after controlling for income. Party membership is closely associated with working for the government but also appears to increase the propensity to use credit and to boost income from farm- and non-farm enterprises. There are strong gender effects: Men are several times more likely to be party members than women are, and the effects of membership on income and subjective well-being are only present among men. Overall, results confirm that in spite of pro-market, economic reforms, Communist Party membership continues to be of high value in rural Vietnam.